Pemberdayaan Lansia melalui Pelatihan Akupresur Mandiri untuk Mengurangi Gangguan Tidur (Insomnia) - Kurnia Eka Putri; Joko Tri Haryanto; Nurmila Mutiah (Rena Cipta Mandiri, 2026)
Insomnia is one of the most common health problems among older adults and can significantly reduce their quality of life if not properly managed. One non-pharmacological intervention that can be applied is self-acupressure. This community service program aimed to improve older adults’ knowledge and skills in performing self-acupressure and to enhance sleep quality among elderly participants at Posyandu Lansia Sejahtera Abadi IX, Gonilan, Kartasura, Sukoharjo. The program was conducted from March to April 2026 and consisted of health education sessions, self-acupressure training on Shenmen (HT7), Sanyinjiao (SP6), Anmian (EX-HN22), and Yintang (EX-HN3) acupoints, followed by four weeks of guided practice and monitoring. Program evaluation was carried out using pre-test and post-test assessments of participants’ knowledge, an observational checklist for acupressure skills, and the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality. The results demonstrated an increase of more than 20% in participants’ knowledge scores, while over 80% of participants were able to perform self-acupressure correctly and independently. Furthermore, more than 70% of participants showed a reduction in PSQI scores, indicating improved sleep quality. In addition to improving sleep quality, the program enhanced participants’ self-care capacity and strengthened the role of community health volunteers in supporting elderly health promotion. Self-acupressure training proved to be a simple, safe, and feasible intervention with strong potential for integration into routine elderly health service programs to promote healthy aging and improve the quality of life of older adults.